Direct UV written waveguides and Bragg gratings in doped planar silica using a 213 nm laser. Issue 8 (2nd March 2021) - Ahmed, Q. Salman; Gow, Paul C.; Holmes, Christopher; Mennea, Paolo L.; Field, James W.; Bannerman, Rex H.S.; Smith, Devin H.; Gawith, Corin B.E.; Smith, Peter G.R.; Gates, James C.
Abstract: In this paper, the first demonstration of simultaneous UV written Bragg gratings and waveguides in germanium and boron‐doped planar silica is presented using a 5th harmonic solid‐state nanosecond laser operating at 213 nm wavelength. The fabrication of high‐quality gratings by using a high peak power density, yielding sufficient uniformity and without any surface damage is demonstrated. The photosensitivity of the doped silica layer is investigated by measuring the local effective refractive index of the optical modes. The written gratings are used to measure grating refractive index modulation, grating detuning bandwidth and the waveguide propagation loss with a minimum value of 0.28 ± 0.07 dB cm − 1 . This paper shows that this new generation of pulsed UV lasers is a promising alternative for conventional longer wavelength CW laser sources used in small spot direct grating writing in doped silica.